Tunisia : 2010 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Tunisia. (IMF Staff Country Reports; Country Report ;, 2010)
Over the last two decades, Tunisia has carried out a wide ranging reform program based on improving the competitiveness of the economy, enhancing the business environment, and increasing trade openness. Tunisia weathered the international crisis relatively well. Tunisia growth could reach 3.8 percent in 2010 if global growth recovers as expected. Prudent fiscal policy in 2010 can be geared toward supporting growth and mitigating the impact of the weak global environment. The tax regime could become more business-friendly.